Developing and evaluating clinical leadership interventions for frontline healthcare providers: a review of the literature - Solange Mianda; Anna Voce (BMC, 2018)
Abstract Background The importance of clinical leadership in ensuring high quality patient care is emphasized in health systems worldwide. Of particular concern are the high costs to health systems related to clinical litigation settlements. To avoid further cost, healthcare systems particularly in High-Income Countries invest significantly in interventions to develop clinical leadership among frontline healthcare workers at the point of care. In Low-Income Countries however, clinical leadership development is not well established. This review of the literature was conducted towards identifying a model to inform clinical leadership development interventions among frontline healthcare providers, particularly for improved maternal and newborn care. Methods A structural literature review method was used, articles published between 2004 and 2017 were identified from search engines (Google Scholar and EBSCOhost). Additionally, electronic databases (CINHAL, PubMed, Medline, Academic Search Complete, Health Source: Consumer, Health Source: Nursing/Academic, Science Direct and Ovid®), electronic journals, and reference lists of retrieved published articles were also searched. Results Employing pre-selected criteria, 1675 citations were identified. After screening 50 potentially relevant full-text papers for eligibility, 24 papers were excluded because they did not report on developing and evaluating clinical leadership interventions for frontline healthcare providers, 2 papers did not have full text available. Twenty-four papers met the inclusion criteria for review. Interventions for clinical leadership development involved the development of clinical skills, leadership competencies, teamwork, the environment of care and patient care. Work-based learning with experiential teaching techniques is reported as the most effective, to ensure the clinical leadership development of frontline healthcare providers. Conclusions All studies reviewed arose in High-Income settings, demonstrating the need for studies on frontline clinical leadership development in Low-and Middle-Income settings. Clinical leadership development is an on-going process and must target both novice and veteran frontline health care providers. The content of clinical leadership development interventions must encompass a holistic conceptualization of clinical leadership, and should use work-based learning, and team-based approaches, to improve clinical leadership competencies of frontline healthcare providers, and overall service delivery.